Prevalence and Antibiotic Susceptibility of Gram-Negative Bacteria: A Study in ICU of Lahore General Hospital, Lahore with Mac Conkey Growth Medium - Ghaffar Ali, Aqeela Ashraf, Zafar Iqbal, Usman Mustafa, Beenish Sarfraz, Sheema Yousaf, Dil Nawaz Khalil (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: Antibiotic sensitivity of gram-negative bacteria responsible for infections on Mac Conkey medium Methodology: Blood samples were cultured on MacConkey medium and antibiotic sensitivity was done by the technique called disk diffusion. Sample size: 200 subjects Duration of research: Four months i.e. 01-09-2022 to 31-12-2022 Results: 148 were gram-negative bacteria, 25 having growth of mixed types and there was no growth in 27cases. In 148 subjects, resistance for ceftriaxone, ceftazidime, imipenem, meropenem, and doxycycline was 79%, 75.6%, 58.7%, 65.5% and 51.3% respectively. Gram-negative bacteria had high resistance %age of cefotaxime and the low for doxycycline. Conclusion: By gram staining technique, cases were all gram-ve bacteria. A species of Klebsiella was originated frequently in blood sample i.e. 18.5%. Keywords: Incidence, antibiotic sensitivity, infection in blood, gram-ve species